FEA of SAW penetration of Ramor 500 steel - Gur, Ali Kaya; Taskaya, Semih; Shankar, Subramaniam; Mohanraj, Thangamuthu (Carl Hanser Verlag, 2020)
Ramor 500 steel plates are used as a ballistic material due to their greater hardness and strength properties. This steel can be produced with a 2-30 mm thickness sheet which may attain 505-590 HV hardness. In the present work, Ramor 500 steel pairs are joined using a submerged arc welding (SAW) process and taking various parameters into consideration. An austenitic additional wire is used for the welding process which contains Cr, Ni, and Mn. The source model prototype was developed using ANSYS software and considering a time-dependent three dimensional thermal model with source cooling. The highest tensile stress voltage value was determined in the sample applying a constant current of 250 A, 25 V and 30 cm x min(-1) welding speed. It was observed that the welding seam width increases as welding tension grows and that welding height and depth increase and decrease more or less in tandem. A ANSYS thermal cooling analysis revealed that welding tension grows with heat transfer which increases 15 mm from the main center of the welding area.
Keywords: Thermal cooling; finite element analysis; steel Ramor 500; penetration; submerged arc welding